Design for Six Sigma: Approach for reliability and low-cost manufacturing (Diseño para Seis Sigma: Enfoque para la fiabilidad y fabricación de bajo costo) - Cruz Álvarez, Jesús Gerardo (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. The aim of this study is to discuss new product development based on a traditional stage-gate process and to examine how new product development [NPD] tools, such as lean design for Six Sigma, can accelerate the achievement of the main goals of NPD: reliable product quality, cost-effective implementation, and desired time-to-market. These new tools must be incorporated into a new approach to NPD based on the Advanced Product and Quality Planning methodology.